Soil recovery of alluvial gold mine spoils in the Peruvian Amazon using Stylosanthes guianensis, a promising cover crop - Velásquez Ramírez, Manuel Gabriel; Castillo Torres, Dennis del; Guerrero Barrantes, Juan Antonio; Vásquez Bardales, Joel; Thomas, Evert; Cusi Auca, Edgar; Chinen Gushiken, Midori; Muñoz Diaz, Betzy; Russo, Ricardo; Corvera Gomringer, Ronald (Wiley, 2021)
The Amazon is an important reservoir of biodiversity and carbon but it is under pressure by multiple threats such as artisanal and small-scale gold mining (ASGM). In Peru ASGM has degraded 90,000 ha of old growth forest since the eighties, leaving vast areas as wastelands. As most ASGM in the region is illegal, efforts to recover degraded areas have been scant. Here we assessed the potential of Stylosanthes guianensis to recover soil health as a first step in the restoration of gold mine spoils in a Native community and a mining concession in Madre de Dios, Peru. We evaluated plant growth and analyzed changes in physical, chemical and biological soil parameters. After 470 days after sowing, average plant height was 46.7 cm with a survival rate > 50% and yields of 23.9 t ha−1 and 450 kg ha−1 of dry biomass and nitrogen, respectively. Multiple soil parameters increased significantly, including cationic exchange capacity (3.3 to 4.0 cmol [+] kg−1), soil organic matter (0.03 to 0.39%), soil respiration (0.02 to 0.06 mg CO2 g−1 d−1) and biomass (0.03 to 0.15 mg C g−1). Soil macrofauna increased from 2 to 11 taxonomic groups, including ants, considered as soil engineers. Furthermore, S. guianensis increased soil carbon sequestration of impacted areas from 0.004 t C ha−1 by more than 1650%, up to 0.07 t C ha−1. These promising findings clearly illustrate S. guianensis potential to kick-start natural succession of Amazonian forests after degradation by ASGM and hence help achieving the Sustainable Development Goals.